Derek Attridge in conversation - Attridge, Derek; Bayot, David Jonathan Y.; Guevara, Francisco Roman (Manila De La Salle University Publishing House, 2015)
"This volume of conversation not only provides a succint philosophical biography that highlights the wide range of Attridge's interests.It likewise foregrounds his energetic engagements with literary theory, poetics, and stylistics, as well as his reassessments of contemporary philosophy and literary ideas, specifically those pertaining to the work Jacques Derrida, James Joyce and J.M. Coetzee. Readers will find in this book a wonderful balancing act as Attridge negotiates the dynamics between the orthodoxies of critical practice and the strategic interventions of deconstructive reading."--Back Cover
Published and distributed in the Philippines under ISBN 978-971-555-612-5 by De La Salle University Publishing House.
This edition published and distributed in Great Britain in 2015 by Sussex Academic Press.
Includes bibliographical references and index.
Keywords: Criticism; Attridge, Derek -- Criticism and interpretation; Literature -- History and criticism